Aktivisme Kelas Menengah Berbasis Media Sosial: Munculnya Relawan dalam Pemilu 2014 - Wasisto Raharjo Jati (Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
Emergence of voluntarism power that occured in 2014 election have indicated new form of middle class in Indonesia. Analyse on middle class always posited as either "leisure class" or "depedent class". However, in 2014 election, its class hass been transformed itselft as powerful actor from extra-parliamentary arena which able to persuade political succesion with Jokowi as pivotal person. Addresing to recent middle class, using of social media undoubtely become main factor to encouraging political awareness from middle class to be partisan voters. This article using cyberactvism perspective to elaborate more deeply toward middle class power in 2014 election.